1998
DOI: 10.1017/s0022143000002422
|View full text |Cite
|
Sign up to set email alerts
|

The structural glaciology of Kongsvegen, Svalbard, and its role in landform genesis

Abstract: Mapping of the structural glaciology of Kongsvegen, Svalbard, reveals cvidence for four main deformational structures. These are stratifi cation, longitudina l foli ation, thrusts a nd crevasse traces. These structures a re considered in terms of th eir contribution to debris entrainment, transport a nd subsequ ent landform development. Stratification is associated with sm a ll amounts of supraglacial debri s that has been folded with fl ow-pa rall el axes; longitudin al foliati on in pl aces incorporates basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 23 publications
(5 reference statements)
2
82
0
1
Order By: Relevance
“…This material is then exposed during the quiescent phase as characteristic landformsediment assemblages or surge landsystems [cf., Rea, 1999, 2005]. Sediment is also exposed within the ice as englacial debris inclusions or bands [e.g., Glasser et al, 1998;Woodward et al, 2002], hereafter referred to as debris-rich englacial structures. Better understanding of the links between surging, debris entrainment, and geomorphology is important as it can help to provide an insight into processes acting at the bed [Christoffersen et al, 2005;Larsen et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This material is then exposed during the quiescent phase as characteristic landformsediment assemblages or surge landsystems [cf., Rea, 1999, 2005]. Sediment is also exposed within the ice as englacial debris inclusions or bands [e.g., Glasser et al, 1998;Woodward et al, 2002], hereafter referred to as debris-rich englacial structures. Better understanding of the links between surging, debris entrainment, and geomorphology is important as it can help to provide an insight into processes acting at the bed [Christoffersen et al, 2005;Larsen et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Two main mechanisms have been proposed for the origin of upglacier-dipping structures: (1) debris-bearing thrust faults originating from the bed in a zone of longitudinal compression [e.g., Hambrey and Dowdeswell, 1997;Glasser et al, 1998;Lønne, 2006;Larsen et al, 2010] and (2) the deformation of structures initially formed as vertical crevasse squeezes, which are then reoriented in a down-ice direction during quiescent phase ice flow. This forms a favorably inclined slip plane along which thrust-style displacement (TSD) can occur during a subsequent surge Woodward et al, 2002;Rea and Evans, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…The entrainment of debris at glacier beds, and its subsequent transport, also provides an important supply of material to the margins. Such entrainment, elevation, and transport is likely to be most effective under warm-based conditions, which facilitate the development of debris-rich basal ice sequences (Sharp et al, 1994;Knight, 1997), debris-rich shear planes (Glasser et al, 1998), and injections of debris into basal crevasses (Rea and Evans, 2011). It is suggested that the entrainment of subglacial debris is particularly efficient on the adverse slopes of overdeepenings, where supercooling processes result in the formation of debris-rich basal ice (Cook et al, 2010) and debris is entrained and elevated via shear planes (Swift et al, 2002).…”
Section: Supply Of Debris To Glacier Marginsmentioning
confidence: 99%
“…Material released from this folded ice can be observed on the ice surface as a medial moraine set, that is subparallel to ice fl ow. Secondly, fractures transverse to the ice fl ow are connected mostly with trusting and shearing processes Glasser et al, 1998) and compressive ice fl ow. This compression is typical for the snout part and for the zone between warmer and colder part of a glacier -in case of polythermal valley glaciers (Lucas, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The role of ice structure in landforms development has been slightly studied (Boulton, 1967(Boulton, , 1972Hambrey et al 1997Hambrey et al , 1999Glasser et al, 1998;Lucas, 2005;Graham et al, 2007;Lucas, 2007) and some papers only mention this problem (e.g. Lyså & Lønne, 2001).…”
Section: Introductionmentioning
confidence: 99%